Reproducción vegetativa y número cromosómico de Adesmia bijuga Phil. (Fabaceae), una especie endémica en peligro crítico de la Región del Maule, Chile - Gómez, Persy; Baeza, Carlos M.; Hahn, Steffen (Gayana Botánica, 2016)
In this note the vegetative reproduction and chromosome number of Adesmia bijuga Phil., an endemic shrub of Central Chile, that is classified as a critically endangered species, is investigated. Our results indicate a positive response of A. bijuga to the shoot rooting by means of promoting hormones. The chromosome number of A. bijuga is 2n = 20. Most of the chromosomes are metacentrics and of small size.